Fermentation factors optimization to enhance yeast performance in producing high yield of bioethanol - Mohd Noor, Siti Fatimah; M, Aida; Nurul JMMA,; Siti MS, (Multidisciplinary Applied Research and Innovation, 2021)
The decreasing in number by year of fossil fuel has bring attention to the world as it has been identified as future challenge. To avoid depletion of fossil fuel, the fermentation of Oil Palm Trunk extraction by Saccharomyces cerevisiae added with sterile mature coconut water can produce a very efficient amount of bioethanol. The purpose of adding mature coconut water (MCW) which act as additive is to magnify the fermentation process in yeast. There are few methods of sterile used such as pasteurization, autoclaving and filtration in order to preserve the natural nutrient content of MCW. On top of that, this review article is an attempt to gather the research findings about effect of natural nutrient content of MCW after undergo suitable sterilization methods. With that, the most suitable method chosen is filtration as the process does not introduce any heat supply which will not cause any nutrient denature even as pasteurization and autoclave where those are focusing on heat and steam. As the nutrient preserved adding into fermentation microbe, the fermentation resulted in higher amount of bioethanol production. Hence, this proved that the optimized fermentation performance is by adding the filtered natural nutrient of MCW in S. cerevisiae  to enhance the production of high yield of bioethanol.